THEORETICAL AND METHODOLOGICAL CONCEPT OF HISTORY AS A SYSTEM OF "MENTAL DIVISIONS" BY ROBERT VIPPER - Nechukhrin, Olexander; Sinjakov, Serhii (Proceedings of the National Aviation University Series Philosophy Cultural, 2024)
The article deals with the methodological scheme introduced by R. Vipper, a well-known historian and historical philosopher. The process of historical cognition, mechanisms and principles of work with historical sources are distinguished in the given article. Topicality of R. Vipper’s work is revealed by providing critical analysis of modern results of historical knowledge.